Pemupukan SP36 pada Lahan Regosol Bereaksi Masam Terhadap Pertumbuhan dan Hasil Dua Varietas Kacang Tanah (Arachis hypogea L.) - Amin Zuchri (Universitas Trunojoyo Madura, 2009)
The aim of this research was to know the effect phosphate dosage on a regosol soil to peanut variety growth and yield. The research was conducted in peanut field. It used a Randomized Complete Block Design (RCBD) ordered faktorially and consisted of two faktor with three replication. The first faktor was the fertilizer dosage of phosphorus of 0, 125, 250 and 325 kg ha-1 of SP36 respectively. The second faktor was the peanut variety of genol and bima variety. The result showed that amount of phosphorus influence to growth of peanut variety, especially: the amount of branches and leaves (8, 11 weeks after planting), dry matter (dm) of leaves, branch and all plant, dry matter of pod per plant. The phosphate dosage of 325 kg ha-1of SP36 result the best of growth and yield (dm of pod per plant) peanut. The genol variety of peanut have the best of amount of branch, leaves, dm leaves, branch and all plant, percentase of flowers to pod, weigth of 100 seeds. The bima variety is only the best to amount of seed per pod and per plant.